인터넷 댓글조작과 형사책임 - 이주일(Ju-Il Lee) (한국컴퓨터정보학회논문지, 2018)
The purpose of this paper is to introspect again the role of the criminal law at a time when it is said that numerous criminal and legal discussions are needed to develop the so called "reply manipulation " case that is shaking the nation's political history. The research method considered the literature and precedents discussed in the past, and discussed the issue of subculture abuse caused by the internet, which is a product of convenience and affluence that came with the Forth industrial revolution through criminal law. Through a computer program, a discussion was held on what penalties would be imposed on the criminal law for attempting to manipulate public opinion by manipulating the so-called number of comments or Reaction. Question of whether the criminal law should further emphasize the need for a discussion on the need for a method to strengthen the preventive functions of the criminal law and expand the scope of punishment in order to address new causes of risk that came with the development of science. Without reflecting on whether such as "government-inspired demonstration "would be possible in today's world that was in the public perception of the authoritarian government of the past, it is a problem to see that the political goals of a particular group can be achieved by manipulating comments or creating public opinion on the Internet. The duty of criminal law is to protect the interests of the law. The role of the criminal law should be maintained the self limiting as far as possible in cases of violation or danger of the law. Still, it is a problem that the role of the criminal justice system today is too aggressive and is seen as a top tool rather than a last resort for solving problems. he role of the internet will be expanded further in the Hyper Connected society. To solve these problems, we should look forward to a change in the priority of other laws and policies other than criminal law. KCI Citation Count: 1